Root Distribution of Different Grapevine Rootstocks on a Relatively Saline Soil - Southey, J.M. (South African Journal of Enology and Viticulture, 2017)
Distribution of roots of Chenin blanc grafted onto 10 different rootstocks on a relatively saline, sandy clayloam with a varying electrical resistance was investigated. Root distribution was similar for all cultivars in that the majority of roots were found in the shallower soil layers (<600 mm), where electrical resistance was relatively high. Restriction of root growth in the deeper soil layers appeared to enhance growth of particularly the finer roots, closer to the soil surface. Root number varied with rootstock cultivar, the highest root numbers being found with 216/3 Castel and 1103 Paulsen and the lowest with US 16-13-23 and Ramsey. Above-ground growth and root density of the rootstocks were found to be in balance.